Draft Genome Sequence of Marine-Derived Streptomyces sp. TP-A0873, a Producer of a Pyrrolizidine Alkaloid Bohemamine - Komaki, Hisayuki (Genome Announc, 2015)
Streptomyces sp. TP-A0873, isolated from deep-sea water, produces three different classes of secondary metabolites: antimycin, bohemamine, and alkylated butenolides. In order to assess the biosynthetic potential of this strain, draft genome sequencing was carried out. The genome contained at least 14 gene clusters for polyketide synthase (PKS) and nonribosomal peptide synthetase (NRPS).